User Satisfaction Analysis of the South Sumatra Spatial Planning Information System (SITARUNG): Generation Z Perceptions Using WebQual 4.0 and IPMA - Umar Rahman Zidan; Ari Wedhasmara; Rizka Dhini Kurnia; Mira Afrina (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Website quality is an important factor in user satisfaction with digital public services. The South Sumatra Spatial Planning Information System (SITARUNG) has not previously been evaluated from a user perspective. This study examines the effects of the WebQual 4.0 dimensions—usability, information quality, and service interaction quality—on user satisfaction with the SITARUNG website and identifies improvement priorities using Importance Performance Map Analysis (IPMA) based on the perceptions of Generation Z users. Using a quantitative survey design, data were collected from 100 Generation Z respondents through a web-based questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4, followed by IPMA to identify indicators requiring improvement. The results show that information quality and service interaction quality significantly and positively influence user satisfaction, whereas usability does not have a significant effect. The model explains 51.6% of the variance in user satisfaction. IPMA identified five indicators in Quadrant I as improvement priorities: relevance of information to user needs (IQ3), appropriateness of information detail (IQ5), accuracy of service delivery information (SIQ1), ease of data management (SIQ2), and website processing and display speed (SIQ4). These findings indicate that information quality and service interaction quality are the primary factors associated with user satisfaction in the SITARUNG website, while usability does not show a significant effect in the present sample. Practically, the findings provide recommendations for improving spatial information services through continuous data updates, adequate GIS server infrastructure, and cross-agency data validation to support the accuracy of public spatial information.